Supratentorial Endodermal Cysts: Review of Literature and Case Report - Caruso, Riccardo; Artico, Marco; Colonnese, Claudio; Marrocco, Luigi; Wierzbicki, Venceslao (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Supratentorial endodermal cysts are very rare pathological entities. Their pathoembryology is largely unknown and they can represent a diagnostic challenge. A research performed on the PubMed database in December 2010, to screen for supratentorial endodermal cyst studies, demonstrated that since 1960 only 31 supratentorial endodermal cysts have been described in the literature, including our case: a 42-year-old woman with a parasellar endodermal cyst. These lesions are usually benign. As with other types of brain cysts, the signs and symptoms caused by supratentorial endodermal cysts are mainly linked to the compression or irritation of surrounding neural structures. Upon neuroimaging examination, they typically appear as a round or lobulated mass. The signal intensity may vary depending on the protein content of the cyst. The majority of reported supratentorial endodermal cysts were completely excised with good or excellent results. Incomplete excision can result in an increased risk of recurrence, infection, and dissemination.
Keywords: endodermal cyst; neurenteric cyst; epithelial cyst; enterogenous cyst; intracranial lesion